2005
DOI: 10.1139/b05-042
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of willow seed dispersal, seed entrapment, and seedling establishment in a heavily browsed montane riparian ecosystem

Abstract: Declines in riparian willow (Salix spp.) communities in Rocky Mountain National Park, Colorado, USA , coincident with a large increase in elk (Cervus elaphus L.) populations, has raised concerns about the future of willow communities. To identify possible constraints on willow establishment in two heavily browsed riparian areas, in 2000 and 2001, we examined seed dispersal phenology, germinability, and the spatial patterns of aerial seed rain, quantified the effects of soil surface relief, texture, and moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 53 publications
1
48
0
Order By: Relevance
“…Maximum willow seed dispersal distances of 2-3 km are much longer than for birch and alder (Schirmer 2006). For this reason, Gage & Cooper (2005) always adopted a background level (i.e., "noise") of 10-30 seeds per m 2 . Nevertheless, the largest densities of deposited seeds were measured at distances of between 30-50 m from willow seed trees (Gage & Cooper 2005 - Fig.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Maximum willow seed dispersal distances of 2-3 km are much longer than for birch and alder (Schirmer 2006). For this reason, Gage & Cooper (2005) always adopted a background level (i.e., "noise") of 10-30 seeds per m 2 . Nevertheless, the largest densities of deposited seeds were measured at distances of between 30-50 m from willow seed trees (Gage & Cooper 2005 - Fig.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Null 2, in contrast, allows species' prevalence to impact their likelihood of colonization. We hypothesized that willow and poplar species are not dispersal limited because their seeds are readily dispersed by wind and water (Gage and Cooper 2005), but we included Null 2 to serve as a more conservative test of community assembly. One drawback of Null 2 is that it is insensitive to situations where rare species (e.g., habitat specialists) co-occur in low species rich communities (Helmus et al 2007).…”
Section: Community Null Modelsmentioning
confidence: 99%
“…It is unclear how many of Rood et al 's (2003) vegetative propagules were a result of beaver forage; as such, detailed comparisons cannot be made to S. sitchensis. Cooper et al (2005) also examined rooted beaver forage and concluded that beaver browse played no role in willow reproduction in Rocky Mountain National Park, Colorado.…”
Section: Asexual Reproduction Through Branch Fragments Was Observed Amentioning
confidence: 99%
“…However, Cooper et al (2005) reported that few beaver dams were being built, as the population had declined substantially over the past 60 years. The impact of beaver on willow reproduction may have been minimal as foraging activity would be slight or non-existent.…”
Section: Asexual Reproduction Through Branch Fragments Was Observed Amentioning
confidence: 99%
See 1 more Smart Citation